Identifikasi Partisipasi Masyarakat Terhadap Pelestarian Hutan Mangrove di Desa Teluk Pambang Kecamatan Bantan Kabupaten Bengkalis (Studi Kasus Kelompok Belukap) - Yuni Elfiza; M. Mardhiansyah '; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Mangrove forest in the TelukPambang Village, Sub District of Bantan, Bengkalis District is managed by KelompokPengelola Mangrove (KPM) Belukap. KPM Belukap is an organization which is formed through a Co- Fish project’s program (rural development programs in the field of fisheries ). KPM Belukap has the purpose of managing mangrove forests (mangroves) that utilization is done wisely to ensure the balance of supply by continuing to maintain and protect the mangrove forest areas, improving the welfare of mangrove wood utilization users, monitoring and oversight of utilization of mangrove forests, as a place of discussion about mangrove forests. This study aims to determine the form and level of community participation, in this case KPM Belukap, to determine the forms of participation and a qualitative descriptive analysis was used and to measure the level of participation Likert scale was used. Analysis of Likert scale is able to indicate clearly the level of participation of members KPM Belukap on each form of participation which are planning , implementation , and utilization . The level of participation was obtained from the factors that influence which are knowledge and expertise , occupation , education , and culture ( the belief in a particular culture). The results showed that the forms of public participation in the preservation of mangrove forests which is managed by KPM Belukap are planning, implementation, and utilization. The level of community’s participation in the conservation of mangrove forests which is managed by KPM Belukap is in the middle participation category with 14 people out of 20 respondents. Keywords: Mangrove Forest, Participation, Conservation, Community